Commemorating the Loyalists in the Loyalist City: Saint John, New Brunswick, 1883–1934 - Marquis, Greg (Urban History Review / Revue d'histoire urbaine, 2004)
Historical consciousness in Saint John, New Brunswick, at present is fragmented. From the 1880s until the mid-1930s, public history was dominated by memories of the 1780s Loyalist founders of the city. This article examines the creation of Loyalist historiography by writers such as Hannay and Raymond, and public commemoration of the Loyalists in a city where most of the population was of non-Loyalist descent. Views of the Loyalists were neither monolithic nor unchanging, but public celebrations stressed their triumph over adversity and contributions to provincial, national, and Imperial progress. The 1904 De Monts-Champlain Tercentenary and the 1927 Irish Famine commemoration were tentative challenges to the dominant historical discourse. The founding of a provincial museum between 1929 and 1934 signalled a shift in public history away from an amateur, voluntary approach to historical knowledge production based on professionals working for the state.